Ultra wideband microwave chaotic oscillator - Panas, A. I. (Publishing House of the KarSU named after E.A.Buketov, 2012)
Development of the effective sources of ultrawideband signals is stimulated by much interest to ultrawideband communication technologies. Chaotic oscillators can play the role of such sources. In the report structure of the microwave ring oscillator capable to generate ultrawideband microwave chaotic signal with uniform power spectral density, is proposed. Its evolution from distributed elements implementation to CMOS IC realization is demonstrated in simulation and experimentally. Dynamics of the basic oscillation modes are investigated, the fact of the chaotic generation is shown. It is demonstrated that such oscillators can be used in different wireless communication applications as a compact device for UWB microwave chaotic signal generation with uniform power spectral density in frequency bandwidth up to 5 GHz and integrated output power reaches about 20 dBm
Keywords: chaotic oscillator; microwave chaotic signal; ultra wideband signals; power spectral density; frequency band